Childhood trauma is associated with elevated anhedonia and altered core reward circuitry in major depression patients and controls. Issue 2 (8th October 2020) - Fan, Jie; Liu, Wanting; Xia, Jie; Li, Sihui; Gao, Feng; Zhu, Jiang; Han, Yan; Zhou, Huan; Liao, Haiyan; Yi, Jinyao; Tan, Changlian; Zhu, Xiongzhao
Abstract: Childhood trauma (CT) is a well‐established risk factor for major depressive disorder (MDD). However, the underlying mechanism linking CT and MDD remains not fully understood. The present study tested the hypothesis that CT have effects on specific types of anhedonia in depression via reward system. To do so, we evaluated different aspects of anhedonia and resting‐state functional connectivity (FC) in reward system among 66 patients with MDD (44 with moderate‐to‐severe and 22 with no or low CT), and 57 healthy controls (HC; 23 with moderate‐to‐severe and 34 with no or low CT). Results showed that MDD patients with moderate‐to‐severe CT suffered more severe state anhedonic depression than patients with no or low level of CT. Individuals with moderate‐to‐severe CT, irrespective of MDD diagnosis, had elevated physical, social and anticipatory but not consummatory trait anhedonia, and demonstrated decreased left nucleus accumbens (NAcc)‐right orbital frontal cortex (OFC) and left ventral caudate‐left OFC connectivity compared to those with no or low exposure. Left NAcc‐right OFC connectivity mediated relationship between CT and state anhedonia in MDD. The total altered ventral striatum (VS)‐OFC connectivity mediated links between CT and physical trait anhedonia in HC. These findings highlight specific types of anhedonia and the core reward system as targets of CT. Blunted hedonic responses via decreased coupling within core reward system may be involved in the mechanism of depression following CT. Implications for clinical interventions are also discussed. Abstract :